Influence of traditional graphics integration on information system user experience: Investigating the mediating role of interaction systems and the moderating role of national graphics standards - Wu, Aifeng (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of traditional graphics on the user experience (UX) in digital interfaces by integrating cultural visual elements to evaluate usability. Symbols that were categorized based on the score of Cultural Representation Score (CRS), Graphical Complexity Index (GCI), and Usability Compatibility Factor (UCF) and ranked based on the score of Weighted Graphical Index (WGI) turned out to be calligraphic symbols with a WGI score of 8.3. The use and comparison of three interface prototypes: Baseline System (BS), Moderate Integration System (MIS), and High Integration System (HIS) with user testing showed that HIS has significantly improved UX metrics such as a reduction in task completion time (19.8s), a lower error rate (2.8%), as well as a higher user engagement index (85.4). Structural Equation Modeling (SEM) tested that Graphical Integration (GI) and Interaction Efficiency (IE) were different from UX (R² = 0.79, p < 0.001). In addition, UX scores were further boosted with compliance with national graphic standards (NGS) as HIS achieved 89.6 in high compliance settings. HIS processed eye fixation data better and performed the scan path shorter than the control. Likewise, one-way ANOVA (p < 0.001) confirmed a significant UX difference, while Cronbach’s Alpha (0.87) was rated as reliable. They provided qualitative insights into how they can provide the feeling of a stronger cultural affinity, intuitive navigation, and an aesthetically pleasing experience. This emphasizes the importance of the strategic integration of the graphics used in digital platforms along with the use of graphics in traditional forms to improve usability and cross-cultural communication. Long-term cognitive effects in different digital environments should be explored in future studies.